The Effect of Nusinersen Therapy on Laboratory Parameters of Patients with Spinal Muscular Atrophy - Sarıkaya Uzan, Gamze; Paketçi, Cem; Günay, Çağatay; Edem, Pınar; Özsoy, Özlem; Hız Kurul, Semra; Yiş, Uluç (Neuropediatrics, 2022)
Introduction We evaluated the effect of nusinersen on clinical and laboratory parameters and presented its safety and effect on laboratory parameters.Methods Two groups were formed from among patients with spinal muscular atrophy (SMA) followed up between September 2017 and June 2021: group 1, SMA type 1; group 2, SMA type 2 and 3. The laboratory parameters were evaluated in groups 1 and 2 between doses. Motor scale tests were performed on patients before each dose of nusinersen.Results Twenty seven patients (group 1; n = 13, group 2; n = 14) were included. The mean age (±standard deviation) at the onset of symptoms was 3 ± 1.21 (range, 1.5–6) months in group 1 and 12 ± 4.27 (range, 8–24) months in group 2. No significant laboratory treatment-related abnormalities and adverse effects were observed. The cerebrospinal fluid protein levels and the frequency of conventional LP were higher in group 1. Serum creatinine (Cr) levels were higher in group 1 before the first dose and higher in group 2 before the fifth dose (p < 0.05). With treatment, the Cr levels of group 1 decreased and group 2 remained constant or increased. We observed that the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders and Hammersmith Functional Motor Scale-Expand scores increased as our patients received treatment (p < 0.05).Conclusion Our results support the safety and efficacy of nusinersen. However, changes in Cr levels according to the clinical type and treatment suggested that serum Cr could be a candidate marker for treatment follow-up.
Keywords: nusinersen; spinal muscular atrophy; safety; effectiveness; creatinine